Evidence From Galactic Cosmic Rays That the Sun Has Likely Entered a Secular Minimum in Solar Activity - F. Rahmanifard; A. P. Jordan; W. C. deWet; N. A. Schwadron; J. K. Wilson; M. J. Owens; H. E. Spence; P. Riley (Space Weather)
Abstract Since the beginning of the space age, the Sun has been in a multi‐cycle period of elevated activity (secular maximum). This secular maximum is the longest in the last 9300 years. Since the end of solar cycle 21 (SC21), however, the Sun has shown a decline in overall activity, which has remarkably increased the fluxes of galactic cosmic rays (GCRs). Here, we investigate the correlation between the modulation of GCRs, the heliospheric magnetic field, and solar wind speed for the last 24 solar cycles to find trends that can potentially be used to predict future solar activity. Specifically, we develop a tool for predicting future magnetic field intensity, based on the hysteresis in the GCR variation, during the last phases of the current cycle. This method estimates that SC25 will be as weak as or weaker than SC24. This would mean that the Sun has likely entered a secular minimum, which, according to historical records, should last for another two cycles (SC25 and SC26).